A sulfide solid electrolyte material and its preparation method and application
Through the coating modification of uniformly distributed oxygen elements in sulfide solid electrolyte, the problem of degradation of stability and conductivity of sulfide electrolyte in the air is solved, and efficient preparation of sulfide electrolyte materials is achieved, suitable for large-scale production and improvement Battery performance.
Patent Information
- Application Number
- CN202311767561.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-12-20
AI Technical Summary
The existing sulfide solid electrolytes are prone to react with water when exposed to air to produce toxic gases, resulting in a decrease in ionic conductivity. The existing improved methods such as the three-layer core-shell structure is complex and difficult to batch prepare, and it is difficult to maintain high ionic conductivity at the same time. Good air stability.
The solution method is used to combine the sulfide solid electrolyte with the oxygen-containing lithium compound coating material. By uniformly distributing oxygen elements on the surface and inside of the electrolyte particles, the air stability and conductivity of the electrolyte are improved, and high-stability electrolyte is formed by high-temperature sintering.
The high ionic conductivity and good air stability of sulfide solid electrolyte materials are achieved, the overall concentration of oxygen elements is reduced, the preparation process is simplified, and the compatibility of electrolytes and positive electrode materials is optimized.
Smart Images

Figure CN117613369B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a sulfide solid electrolyte material and a preparation method and application thereof. Background Art
[0002] Compared with traditional electrolytes, solid electrolytes have higher capacity and better safety. Among them, sulfide solid electrolytes have attracted much attention in recent years due to their advantages such as high safety, high ionic conductivity, and wide electrochemical window.
[0003] There are multiple PS bonds in sulfide solid electrolytes, which makes them very easy to react with H2O when exposed to air, producing toxic H2S gas. The ionic conductivity of the electrolyte decreases significantly after the structure is destroyed. The literature (EnergyEnviron.Sci.7,1053–1058(2014)) records that the soft and hard acid-base theory is used as the design idea. Under this guidance, Sn 4 + 、As 5+ , Sb 5+ and other soft acids tend to react with soft bases S 2- Tightly bonding to resist the erosion of H2O has been used to improve the air stability of sulfide electrolytes. Similarly, replacing part of S with O can also improve the air stability of sulfide electrolytes. In addition, the use of surface coating can also effectively isolate the electrolyte from the reaction of H2O in the air, and the coating layer can improve the compatibility of the electrolyte layer with the positive electrode material and inhibit the generation of the space charge layer.
[0004] Chinese patent CN117059880A uses waxy solid organic matter and lithium-containing compounds to coat the electrolyte material. Although it can improve the air stability of the electrolyte material to a certain extent, the decrease in conductivity is very obvious.
[0005] Chinese patent CN110400967A prepares a three-layer core-shell sulfide solid electrolyte. The outermost layer contains a higher concentration of oxygen, which can improve the stability of the electrolyte in the air. However, this three-layer core-shell structure is too complex and difficult to prepare in batches.
[0006] Therefore, there is an urgent need for a new sulfide electrolyte that has both high ionic conductivity and good air stability. Summary of the invention
[0007] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a sulfide solid electrolyte material and its preparation method and application. The sulfide solid electrolyte material of the present invention has oxygen elements on the surface of the electrolyte particles and inside the particles. Compared with the method of only coating on the surface, the sulfide solid electrolyte material of the present invention has better air stability. In addition, compared with the doping of single oxygen, the modified oxygen-containing lithium compound can maintain the conductivity of the sulfide electrolyte. The preparation method of the present invention adopts a solution method to coat and modify the material so that the distribution of oxygen elements is more uniform, which greatly improves the air stability of the sulfide solid electrolyte material and the stability to the oxide positive electrode, and can also greatly reduce the overall oxygen concentration in the electrolyte.
[0008] A first aspect of the present invention provides a sulfide solid electrolyte material.
[0009] Specifically, a sulfide solid electrolyte material includes a sulfide solid electrolyte and a coating material coating the sulfide solid electrolyte, wherein the coating material includes an oxygen-containing lithium compound, and the oxygen-containing lithium compound does not contain Nb and / or Ta.
[0010] Preferably, in the sulfide solid electrolyte material, the mass of the coating material is 0.1-3% of the mass of the sulfide solid electrolyte, and more preferably 0.1-2%.
[0011] Preferably, the sulfide solid electrolyte is selected from Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li 3.85 Sn 0.85 Sb 0.15 S4, Li 3.8 Sn 0.8 As 0.2 S4, Li 3.25 Ge 0.25 P 0.75 S4、Li4Sn 0.9 Si 0.1 S4, Li 10 SnP2S 12 、Li7GePS8、Li 3.25 P 0.95 S4, Li 11 Si2PS 12 , Li7P2S8I, 75Li2S·21P2S5·4P2O5, 70Li2S·29P2S5·1P2O5, Li 6.8 Si 0.8 As 0.2S5I、Li 9.54 [Si 1-δ M δ ] 1.74 P 1.44 S 11.1 Br 0.3 O 0.6 , where M = Ge, Sn; 0≤δ≤1; Li (7-a) PS (6-a) X a , wherein 0.5≤a≤1.75, X is at least one of the halogen elements, Li3PS4, Li 10 GeP2S 12 、Li7P3S 11 , Li4SnS4, or at least one of the following.
[0012] Preferably, the coating material is selected from at least one of Li2SO4, Li2CO3, CH3COOLi, LiNO3, Li3PO4, LiHSO4, Li2O, Li2O2, LiClO4, Li2TiO3, Li2AlO3, Li2ZrO3, lithium bis(oxalatoborate), bis(difluorosulfonylimide), lithium difluorophosphate, and lithium 4,6-dichloropyridazine-3-carboxylate.
[0013] Preferably, the ionic conductivity of the sulfide solid electrolyte material is not less than 2.12 mS / cm; further preferably, not less than 3 mS / cm; more preferably, not less than 4 mS / cm.
[0014] Preferably, the attenuation rate of the ionic conductivity of the sulfide solid electrolyte material after being exposed to dry air for 4 hours is less than 12%; further preferably, the attenuation rate is less than 10%; more preferably, the attenuation rate is less than 5%.
[0015] A second aspect of the present invention provides a method for preparing a sulfide solid electrolyte material.
[0016] Specifically, a method for preparing a sulfide solid electrolyte material comprises the following steps:
[0017] (1) dispersing a sulfide solid electrolyte in a solvent to obtain a mixture A;
[0018] (2) adding a coating material to mixture A to obtain mixture B;
[0019] (3) heat-treating the mixture B to volatilize the solvent and obtain an electrolyte precursor;
[0020] (4) calcining the electrolyte precursor to obtain the sulfide solid electrolyte material.
[0021] Preferably, in step (1), the sulfide solid electrolyte is in powder form.
[0022] Preferably, in step (1), the sulfide solid electrolyte is selected from Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li 3.85 Sn 0.85 Sb 0.15 S4, Li 3.8 Sn 0.8 As 0.2 S4, Li 3.25 Ge 0.25 P 0.75 S4、Li4Sn 0.9 Si 0.1 S4, Li 10 SnP2S 12 、Li7GePS8、Li 3.25 P 0.95 S4, Li 11 Si2PS 12 , Li7P2S8I, 75Li2S·21P2S5·4P2O5, 70Li2S·29P2S5·1P2O5, Li 6.8 Si 0.8 As 0.2 S5I、Li 9.54 [Si 1-δ M δ ] 1.74 P 1.44 S 11.1 Br 0.3 O 0.6 , where M = Ge, Sn; 0≤δ≤1; Li (7-a) PS (6-a) X a , wherein 0.5≤a≤1.75, X is at least one of the halogen elements, Li3PS4, Li 10 GeP2S 12 、Li7P3S 11 , Li4SnS4, or at least one of the following.
[0023] Preferably, in step (1), the solvent is selected from at least one of formamide, acetonitrile, trifluoroacetic acid, hexamethylphosphoramide, pyridine, tetramethylethylenediamine, n-butanol, methanol, dimethyl sulfoxide, N,N-dimethylformamide, ethanol, propanol, acetone, dioxane, tetrahydrofuran, methyl ethyl ketone, n-butanol, ethyl acetate, ether, isopropyl ether, dichloromethane, chloroform, ethyl bromide, benzene, carbon tetrachloride, carbon disulfide, and propylene glycol.
[0024] Preferably, in step (2), the coating material is selected from at least one of Li2SO4, Li2CO3, CH3COOLi, LiNO3, Li3PO4, LiHSO4, Li2O, Li2O2, LiClO4, Li2TiO3, Li2AlO3, Li2ZrO3, lithium bis(oxalatoborate), bis(difluorosulfonyl)imide, lithium difluorophosphate, and lithium 4,6-dichloropyridazine-3-carboxylate.
[0025] Preferably, in step (1) and step (2), stirring is performed during the process of obtaining mixture A and mixture B, the stirring speed is 80-800 r / min, and the stirring time is 10-180 min. More preferably, the stirring speed is 100-600 r / min, and the stirring time is 10-180 min.
[0026] Preferably, step (1) and step (2) are carried out under an inert atmosphere (eg, nitrogen or argon).
[0027] Preferably, in step (2), the mass of the coating material is 0.1-3% of the mass of the sulfide solid electrolyte, and more preferably 0.1-2%.
[0028] Preferably, in step (3), the heat treatment temperature is 30-160°C, and the heat treatment time is 0.5-24h; further preferably, the heat treatment temperature is 40-160°C, and the heat treatment time is 0.5-24h.
[0029] Preferably, in step (4), the calcination temperature is 150-700°C, and the time is 0.5-60h; further preferably, the calcination temperature is 160-700°C, and the time is 0.5-60h.
[0030] A third aspect of the present invention provides an application of a sulfide solid electrolyte material.
[0031] An all-solid-state battery comprises the above-mentioned sulfide solid electrolyte material.
[0032] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0033] (1) The sulfide solid electrolyte material of the present invention comprises a sulfide solid electrolyte and a coating material coating the sulfide solid electrolyte, wherein the coating material comprises an oxygen-containing lithium compound, and the oxygen-containing lithium compound does not contain Nb and / or Ta. By coating the sulfide solid electrolyte with a specific type of oxygen-containing lithium compound, a sulfide solid electrolyte material having high ion conductivity, good air stability and good charge-discharge cycle stability is obtained.
[0034] (2) The preparation method of the present invention comprises dissolving a sulfide solid electrolyte and an oxygen-containing lithium compound in a solvent to form a uniform mixed solution, removing the solvent to obtain a mixture precursor of the oxygen-containing lithium compound and the sulfide electrolyte, and sintering at a high temperature to obtain a sulfide solid electrolyte with high stability and high ionic conductivity. This scheme is simple and effective, has a low production cost, and can be mass-produced.
[0035] (3) The present invention adopts a solution method to modify the sulfide electrolyte. This scheme is simple to prepare, has low production cost, and can be prepared on a large scale.
[0036] (4) The present invention adopts a solution method to modify the sulfide electrolyte, which can make the oxygen-containing lithium compound and the electrolyte uniformly mixed. After high-temperature heat treatment, the electrolyte contains oxygen elements both inside and on the surface, which can significantly improve the stability of the electrolyte material in the air. In addition, the presence of oxygen elements can optimize the interface reaction between the electrolyte and the positive electrode material.
[0037] (5) The present invention uses oxygen-containing lithium compounds to modify sulfide electrolytes. After high-temperature treatment, the oxygen-containing lithium compounds can not only make the electrolyte contain oxygen elements inside and on the surface, but the lithium elements in the oxygen-containing lithium compounds can also be used as lithium supplements to improve the performance of all-solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is the XRD diagram of the sulfide solid electrolyte material of Example 1 of the present invention. DETAILED DESCRIPTION
[0039] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0040] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0041] Example 1
[0042] A method for preparing a sulfide solid electrolyte material comprises the following steps:
[0043] (1) In a glove box under a nitrogen atmosphere, 30 g of Li6PS5Cl sulfide solid electrolyte powder was uniformly dispersed in ethyl acetate and magnetically stirred (speed of 100 r / min, time of 10 min) to obtain a mixture A;
[0044] (2) Add 0.03 g of Li3PO4 to mixture A and perform magnetic stirring (speed of 100 r / min, time of 30 min) to obtain mixture B;
[0045] (3) heating the mixture B in a water bath at 40° C. for 0.5 h to completely volatilize the ethyl acetate to obtain an electrolyte precursor;
[0046] (4) calcining the electrolyte precursor at a high temperature of 480° C. for 8 h to obtain a Li6PS5Cl sulfide solid electrolyte material with Li3PO4 coated on the surface.
[0047] Figure 1 This is the XRD diagram of the sulfide solid electrolyte material of Example 1 of the present invention. Figure 1 ( Figure 1 It can be seen from the vertical axis "Intensity" that the prepared sulfide solid electrolyte material has no impurity peak.
[0048] Example 2
[0049] A method for preparing a sulfide solid electrolyte material comprises the following steps:
[0050] (1) In a glove box under a nitrogen atmosphere, 30 g of Li6PS5Cl sulfide solid electrolyte powder was uniformly dispersed in anhydrous ethanol and magnetically stirred (speed of 100 r / min, time of 10 min) to obtain a mixture A;
[0051] (2) Add 0.03 g of Li3PO4 to mixture A and perform magnetic stirring (speed of 100 r / min, time of 30 min) to obtain mixture B;
[0052] (3) heating the mixture B in a water bath at 80° C. for 0.5 h to completely evaporate the anhydrous ethanol and obtain an electrolyte precursor;
[0053] (4) calcining the electrolyte precursor at a high temperature of 450° C. for 8 h to obtain a Li6PS5Cl sulfide solid electrolyte material with Li3PO4 coated on the surface.
[0054] Example 3
[0055] A method for preparing a sulfide solid electrolyte material comprises the following steps:
[0056] (1) In a glove box under a nitrogen atmosphere, 30 g of Li6PS5Cl sulfide solid electrolyte powder was uniformly dispersed in anhydrous ethanol and magnetically stirred (speed of 200 r / min, time of 10 min) to obtain a mixture A;
[0057] (2) Add 0.6 g of Li3PO4 to mixture A and stir magnetically (speed of 100 r / min, time of 30 min) to obtain mixture B;
[0058] (3) heating the mixture B in a water bath at 80° C. for 0.5 h to completely evaporate the anhydrous ethanol and obtain an electrolyte precursor;
[0059] (4) calcining the electrolyte precursor at a high temperature of 400° C. for 8 h to obtain a Li6PS5Cl sulfide solid electrolyte material with Li3PO4 coated on the surface.
[0060] Example 4
[0061] A method for preparing a sulfide solid electrolyte material comprises the following steps:
[0062] (1) In a glove box under a nitrogen atmosphere, 30 g of Li6PS5Cl sulfide solid electrolyte powder was uniformly dispersed in anhydrous ethanol and magnetically stirred (speed of 100 r / min, time of 20 min) to obtain a mixture A;
[0063] (2) adding 0.3 g of Li2ZrO3 to mixture A, and performing magnetic stirring (speed of 100 r / min, time of 30 min) to obtain mixture B;
[0064] (3) heating the mixture B in a water bath at 80° C. for 0.5 h to completely evaporate the anhydrous ethanol and obtain an electrolyte precursor;
[0065] (4) calcining the electrolyte precursor at a high temperature of 450° C. for 8 h to obtain a Li6PS5Cl sulfide solid electrolyte material with Li2ZrO3 coated on the surface.
[0066] Example 5
[0067] A method for preparing a sulfide solid electrolyte material comprises the following steps:
[0068] (1) In a glove box under a nitrogen atmosphere, 30 g of Li6PS5Cl sulfide solid electrolyte powder was uniformly dispersed in anhydrous ethanol and magnetically stirred (speed of 100 r / min, time of 10 min) to obtain a mixture A;
[0069] (2) adding 0.3 g of Li2ZrO3 to mixture A and performing magnetic stirring (speed of 200 r / min, time of 30 min) to obtain mixture B;
[0070] (3) heating the mixture B in a water bath at 80° C. for 0.5 h to completely evaporate the anhydrous ethanol and obtain an electrolyte precursor;
[0071] (4) calcining the electrolyte precursor at a high temperature of 450° C. for 8 h to obtain a Li6PS5Cl sulfide solid electrolyte material with Li2ZrO3 coated on the surface.
[0072] Example 6
[0073] A method for preparing a sulfide solid electrolyte material comprises the following steps:
[0074] (1) In a glove box under a nitrogen atmosphere, 30 g of Li6PS5Cl sulfide solid electrolyte powder was uniformly dispersed in anhydrous ethanol and magnetically stirred (speed of 100 r / min, time of 10 min) to obtain a mixture A;
[0075] (2) adding 0.3 g of Li2ZrO3 to mixture A and performing magnetic stirring (speed of 100 r / min, time of 60 min) to obtain mixture B;
[0076] (3) heating the mixture B in a water bath at 80° C. for 0.5 h to completely evaporate the anhydrous ethanol and obtain an electrolyte precursor;
[0077] (4) calcining the electrolyte precursor at a high temperature of 450° C. for 8 h to obtain a Li6PS5Cl sulfide solid electrolyte material with Li2ZrO3 coated on the surface.
[0078] Example 7
[0079] A method for preparing a sulfide solid electrolyte material comprises the following steps:
[0080] (1) In a glove box under a nitrogen atmosphere, 30 g of Li6PS5Cl sulfide solid electrolyte powder was uniformly dispersed in anhydrous ethanol and magnetically stirred (speed of 100 r / min, time of 10 min) to obtain a mixture A;
[0081] (2) adding 0.3 g of LiNO3 to mixture A and performing magnetic stirring (speed of 100 r / min, time of 30 min) to obtain mixture B;
[0082] (3) heating the mixture B in a water bath at 80° C. for 0.5 h to completely evaporate the anhydrous ethanol and obtain an electrolyte precursor;
[0083] (4) calcining the electrolyte precursor at a high temperature of 400° C. for 8 h to obtain a Li6PS5Cl sulfide solid electrolyte material with LiNO3 coated on the surface.
[0084] Example 8
[0085] A method for preparing a sulfide solid electrolyte material comprises the following steps:
[0086] (1) In a glove box under a nitrogen atmosphere, 30 g of Li6PS5Cl sulfide solid electrolyte powder was uniformly dispersed in anhydrous ethanol and magnetically stirred (speed of 100 r / min, time of 10 min) to obtain a mixture A;
[0087] (2) adding 0.3 g of LiHSO4 to mixture A and performing magnetic stirring (speed of 100 r / min, time of 30 min) to obtain mixture B;
[0088] (3) heating the mixture B in a water bath at 80° C. for 0.5 h to completely evaporate the anhydrous ethanol and obtain an electrolyte precursor;
[0089] (4) calcining the electrolyte precursor at a high temperature of 450° C. for 6 h to obtain a Li6PS5Cl sulfide solid electrolyte material with LiHSO4 coated on the surface.
[0090] Example 9
[0091] A method for preparing a sulfide solid electrolyte material comprises the following steps:
[0092] (1) In a glove box under a nitrogen atmosphere, 30 g of Li7GePS8 sulfide solid electrolyte powder was uniformly dispersed in anhydrous ethanol and magnetically stirred (speed of 100 r / min, time of 10 min) to obtain a mixture A;
[0093] (2) Add 0.3 g of Li3PO4 to mixture A and stir magnetically (speed of 100 r / min, time of 30 min) to obtain mixture B;
[0094] (3) heating the mixture B in a water bath at 80° C. for 0.5 h to completely evaporate the anhydrous ethanol and obtain an electrolyte precursor;
[0095] (4) calcining the electrolyte precursor at a high temperature of 450° C. for 8 h to obtain a Li7GePS8 sulfide solid electrolyte material with Li3PO4 coated on the surface.
[0096] Example 10
[0097] A method for preparing a sulfide solid electrolyte material comprises the following steps:
[0098] (1) In a glove box under a nitrogen atmosphere, 30 g of Li7GePS8 sulfide solid electrolyte powder was uniformly dispersed in anhydrous ethanol and magnetically stirred (speed of 100 r / min, time of 10 min) to obtain a mixture A;
[0099] (2) adding 0.3 g of LiNO3 to mixture A and performing magnetic stirring (speed of 100 r / min, time of 30 min) to obtain mixture B;
[0100] (3) heating the mixture B in a water bath at 80° C. for 0.5 h to completely evaporate the anhydrous ethanol and obtain an electrolyte precursor;
[0101] (4) calcining the electrolyte precursor at a high temperature of 450° C. for 8 h to obtain a Li7GePS8 sulfide solid electrolyte material with LiNO3 coated on the surface.
[0102] Comparative Example 1
[0103] In Comparative Example 1, no coating modification treatment was performed, and Li6PS5Cl electrolyte powder was directly calcined at high temperature. The high temperature calcination temperature was 450° C. and the high temperature calcination time was 8 h to obtain Li6PS5Cl sulfide solid electrolyte.
[0104] Comparative Example 2
[0105] Compared with Example 1, the difference of Comparative Example 2 is that the same amount of LiNb 0.5 Ta 0.5 O3 replaces Li3PO4 in Example 1, and the rest of the process is the same as Example 1.
[0106] Product effect testing
[0107] The ionic conductivity and physical phase of the sulfide solid electrolyte materials of Experimental Examples 1-10 and Comparative Examples 1-2 were measured according to the following method.
[0108] Ionic conductivity determination:
[0109] The sulfide solid electrolyte materials prepared in Examples 1-10 and Comparative Examples 1-2 were pressed into a disk-shaped lithium ion solid electrolyte with a diameter of 10 mm and a thickness of 1 mm under the conditions of a water content of <10 ppm and 200 MPa. EIS test was performed at room temperature 25°C to calculate Li + The calculated results are shown in Table 1.
[0110] XRD test:
[0111] The sulfide solid electrolyte materials prepared in Examples 1-10 and Comparative Examples 1-2 were spread over the sample grooves in turn, and pressed and slid left and right with a glass slide to smooth the sample surface. Double-sided tape was pasted on the grooves up and down, left and right, and a polyimide film was sealed. The test angle was 10-80°, the scanning time was 8 minutes, and the test results are shown in Table 1.
[0112] Table 1
[0113]
[0114]
[0115]
[0116] It can be seen from Table 1 that compared with the unmodified electrolyte material in Comparative Example 1, the ionic conductivity of the sulfide solid electrolyte material modified by the oxygen-containing lithium compound in Examples 1-10 is maintained at a relatively high level, and the ionic conductivity decay rate after exposure to a dry air environment for 4 hours is relatively slow; the physical phase is purer, and no impurity peak appears.
[0117] Production of all-solid-state lithium battery:
[0118] The sulfide solid electrolyte material prepared in Examples 1-10 and Comparative Examples 1-2 is mixed with the positive electrode material (NCM811 high nickel ternary), the conductive agent (VGCF vapor-grown carbon fiber), and the binder (PTFE polytetrafluoroethylene) in a mass ratio of 15:35:2:1, and then rolled into a film, die-cut, and packaged to form a lithium-ion battery positive electrode. A lithium metal negative electrode is selected to assemble the positive electrode and the electrolyte membrane prepared above into a battery, and a cycle performance test is performed to verify whether the modified sulfide solid electrolyte material improves the cycle stability of the battery. The present invention adopts a segmented lamination process, and the positive electrode, solid electrolyte layer and negative electrode are cut into specified sizes and then laminated in sequence for packaging.
[0119] Charge and discharge performance test: The all-solid-state battery was placed at a constant temperature of 25°C and a constant current charge and discharge test was performed at a current density of 0.2C using a BTS-5V10 mA battery test cabinet to obtain the first cycle charge and discharge specific capacity and coulomb efficiency.
[0120] Cycle performance test: The above all-solid-state battery was placed at a constant temperature of 25°C, and charged and discharged for 100 cycles at a current density of 0.5C using a BTS-5V10mA battery test cabinet, and the discharge specific capacity of the 100th cycle was calculated. The test results are shown in Table 1.
[0121] It can be seen from Table 1 that the battery test results show that compared with the unmodified electrolyte material in Comparative Example 1, the battery composed of the sulfide solid electrolyte material modified with the oxygen-containing lithium compound in Experimental Examples 1-10 has significantly higher first cycle charge and discharge specific capacity and discharge specific capacity after 100 cycles.
[0122] In summary, the sulfide solid electrolyte material with a surface coated with an oxygen-containing lithium compound prepared by the present invention has good stability to air and to metallic lithium, and the ionic conductivity is maintained at a high level and decays slowly; at the same time, the battery assembled using the modified electrolyte exhibits better electrochemical performance, because the present invention uses an oxygen-containing lithium compound as a coating material and lithium as a lithium supplement, thereby improving the performance of the all-solid-state battery; the sulfide electrolyte prepared by the present invention has a simple process, low cost, and can be produced on a large scale.
Claims
1. A method for preparing a sulfide solid electrolyte material, characterized in that: The following steps are involved: (1) In a glove box under a nitrogen atmosphere, 30 g of Li6PS5Cl sulfide solid electrolyte powder was dispersed in anhydrous ethanol and stirred with a magnetic stirrer at a speed of 100 r / min for 10 min to obtain a mixture A; (2) Add 0.03 g of Li3PO4 to mixture A and stir magnetically at a speed of 100 r / min for 30 min to obtain mixture B; (3) heating the mixture B in a water bath at 80° C. for 0.5 h to completely evaporate the anhydrous ethanol and obtain an electrolyte precursor; (4) calcining the electrolyte precursor at a high temperature of 450° C. for 8 h to obtain a Li6PS5Cl sulfide solid electrolyte material coated with Li3PO4; or, (1) In a glove box under a nitrogen atmosphere, 30 g of Li6PS5Cl sulfide solid electrolyte powder was dispersed in anhydrous ethanol and stirred with a magnetic stirrer at a speed of 100 r / min for 10 min to obtain a mixture A; (2) adding 0.3 g of Li2ZrO3 to mixture A, and performing magnetic stirring at a speed of 200 r / min for 30 min to obtain mixture B; (3) heating the mixture B in a water bath at 80° C. for 0.5 h to completely evaporate the anhydrous ethanol and obtain an electrolyte precursor; (4) calcining the electrolyte precursor at a high temperature of 450° C. for 8 h to obtain a Li6PS5Cl sulfide solid electrolyte material coated with Li2ZrO3; or, (1) In a glove box under a nitrogen atmosphere, 30 g of Li6PS5Cl sulfide solid electrolyte powder was uniformly dispersed in anhydrous ethanol, and magnetic stirring was performed at a speed of 100 r / min for 10 min to obtain a mixture A; (2) adding 0.3 g of Li2ZrO3 to mixture A, and performing magnetic stirring at a speed of 100 r / min for 60 min to obtain mixture B; (3) heating the mixture B in a water bath at 80° C. for 0.5 h to completely evaporate the anhydrous ethanol and obtain an electrolyte precursor; (4) High temperature calcination of the electrolyte precursor at a temperature of 450°C for 8 h to obtain a Li6PS5Cl sulfide solid electrolyte material coated with Li2ZrO3 or, (1) In a glove box under a nitrogen atmosphere, 30 g of Li6PS5Cl sulfide solid electrolyte powder was dispersed in anhydrous ethanol and stirred with a magnetic stirrer at a speed of 100 r / min for 10 min to obtain a mixture A; (2) adding 0.3 g of LiNO3 to mixture A, and performing magnetic stirring at a speed of 100 r / min for 30 min to obtain mixture B; (3) heating the mixture B in a water bath at 80° C. for 0.5 h to completely evaporate the anhydrous ethanol and obtain an electrolyte precursor; (4) calcining the electrolyte precursor at a high temperature of 400° C. for 8 h to obtain a Li6PS5Cl sulfide solid electrolyte material with LiNO3 coated on the surface.
2. An all-solid-state battery, characterized in that: It includes the sulfide solid electrolyte material prepared by the preparation method according to claim 1.
